Determinants of infarct progression and perfusion core growth in transferred LVO patients from remote regions - Valente, Michael; Bivard, Andrew; Yan, Bernard; Davis, Stephen M.; Campbell, Bruce C. V.; Mitchell, Peter J.; Ma, Henry; Parsons, Mark W. (Frontiers in Neurology, 2024)
Repeat imaging when regional and remote stroke patients arrive at a comprehensive stroke center (CSC) can delay endovascular thrombectomy (EVT). We examined which clinical and imaging parameters predict infarct progression and perfusion core growth during transport.We included patients recruited 2017-2023 in a prospective database who were transferred from remote sites with large vessel occlusion, had CT-perfusion imaging at the primary stroke center (PSC) and had repeat CT on arrival at the CSC demonstrating persistent occlusion. The key imaging characteristics were perfusion core change (rCBF<30%) and ASPECTS change. Multiple and ordinal logistic regression analyses were used to assess the relationship between background clinical and imaging variables and the CT-perfusion core and ASPECTS on arrival. DEFUSE 3 criteria (ASPECTS 6, perfusion core <70ml) was used to define 'favorable imaging'.In 90 patients with CT-perfusion at both PSC and CSC and persistent occlusion, median onset to PSC presentation was 279minutes (IQR 143-702), PSC presentation to CSC arrival was 243.5minutes (IQR186-335) and distance travelled was 186.5km . Lower baseline ASPECTS (per point) was associated with 7ml (95%CI 2-11ml) increase in perfusion core between scans (p=0.004). Time from onset, time between PSC and CSC and distance traveled were not significantly associated with either ASPECTS or perfusion core growth during transport. 11/78 (14%) patients had deterioration of initially favorable imaging profiles during transport.Perfusion core growth during transport was uncommon and most strongly associated with lower ASPECTS at the PSC. Initially favorable PSC imaging may predict whether repeat imaging is necessary at the CSC.